Characteristics of Eco-SB Support with Twisted Angles Using FLAC3D - Noh, J.; Lee, G.; Hirata, A.; Obara, Y.; Jang, Hyong Doo; Kang, Seong-Seung (2017)
This study is to define the characteristics of Eco-SB according to the twisted angles as a multipurpose support which was developed to improve the bearing capacity of the ground. The changes in physical properties between Eco-SB and the ground by the pullout test were analyzed using the FLAC3D numerical analysis. The twisted angles of Eco-SB were varied from 0o to 60oat 10o intervals. From the results of the numerical analysis, the pullout load at 8 mm of displacement by the pullout test was 3.3 kN at the twisted angle of 0o, 7.0 kN of 10o, 7.4 kN of 20o, 7.2 kN of 30o, 8.3 kN of 40o, 11.5 kN of 50o and 18.3 kN of 60o. The pullout load showed almost the same value in the range of twisted angles 10o ~ 30o, and tendency to increase with the twisted angle generally. The maximum shear stress between Eco-SB and the ground was 16.8 kPa at the twisted angle of 0o, 86.7 kPa of 10o, 93.4 kPa of 20o, 85.4 kPa of 30o, 79.9 kPa of 40o, 118.9 kPa of 50o and 184.8 kPa of 60o. The maximum shear stress showed a sharp increase in the range of twisted angles 0o ~ 10o, a slight increase and decrease in the range of 10o ~ 40o and a sharp increase again in the range of 40o ~ 60o.